Development of a polymerase chain reaction (PCR) assay targeted to the dnaJ gene of vibrio harveyi, a bacterial pathogen in asian seabass, lates calcarifer - Caipang, Christopher M. A. (Bioflux SRL, 2011)
Partial sequence of the dnaJ gene of Vibrio harveyi, which was isolated from diseased juvenileAsian seabass, Lates calcarifer was identified. The partial sequence of dnaJ gene of V. harveyi was 447 bp and shared at least 77% identity at the nucleotide level with the dnaJ gene of other Vibrios. It was distinct from the dnaJ gene of other Vibrios but was closely related with the dnaJ gene of V. rotiferianus and V. campbellii having at least 90% nucleotide identity. PCR primers targeting this gene were designed to detect the pathogen in Asian seabass. The assay was specific to V. harveyi and the limit of detection was 100 pg of genomic DNA ml-1 or 100 fg of bacterial genomic DNA in a PCR reaction. Thiscorresponded to a sensitivity of approximately 20 genome equivalents (GE) of V. harveyi. These resultsindicate that the dnaJ gene is a good candidate to develop primers for the PCR assay in detecting V.harveyi in fish.